Sediment Nitrous Oxide Fluxes Are Dominated by Uptake in a Temperate Estuary - Foster, Sarah Q.; Fulweiler, Robinson W. (Frontiers in Marine Science, 2016)
Coastal marine ecosystems are generally considered important sources of nitrous oxide (N2O), a powerful greenhouse gas and ozone depleting substance. To date most studies have focused on the environmental factors controlling N2O production although N2O uptake has been observed in a variety of coastal ecosystems. In this study, we examined sediment fluxes of N2O during two years (2012-2013) in a shallow temperate estuary (Waquoit Bay, MA, USA). Overall sediments were a net N2O sink (-23 ±5.2 nmol m-2 h-1, mean ±SE, significantly less than zero p<0.0001). N2O fluxes were significantly correlated to water column dissolved N2O (% saturation) (p<0.0001), inorganic phosphorus (DIP) (p=0.0017) and nitrogen (DIN) (p=0.0019), as well as to temperature (p=0.0192). Additionally, there was a positive correlation between sediment N2O uptake and both oxygen (O2) and DIP uptake (p=0.0002 and p<0.0001, O2 and DIP sediment uptake, respectively). Results from this study indicate that sediments in shallow coastal ecosystems can be a strong sink of dissolved N2O, and therefore may mitigate N2O efflux to the atmosphere and export to the coastal ocean. Establishing the nature and strength of relationships between environmental conditions and sediment N2O fluxes moves us towards better-constrained models that will improve ecosystem management strategies, N2O budgets, and our ability to predict the response of coastal ecosystems to local and global change. Establishing the nature and strength of relationships between environmental conditions and sediment N2O fluxes moves us towards better-constrained models that will improve ecosystem management strategies, N2O budgets, and our ability to predict the response of coastal ecosystems to local and global change.